Case report: Pediatric patient with severe clinical course of CTLA-4 insufficiency treated with HSCT - Drabko, Katarzyna; Zarychta, Julia; Kowalczyk, Adrian; Cienkusz, Magdalena (Frontiers in Immunology, 2024)
BackgroundCytotoxic T lymphocyte–associated antigen-4 (CTLA-4) insufficiency is a rare disease belonging to inborn errors of immunity. Most cases of patients with CTLA-4 insufficiency are diagnosed in adults, therefore it is not a common problem in the clinical practice of pediatricians. However, it is worth noticing that most cases described in the literature show the first symptoms of the disease before the age of 18, but the phenotypic variability of patients complicates and delays the diagnostic process.Case descriptionHerein, we report a case of an almost 4-year-old patient whose first symptom of CTLA-4 insufficiency was thrombocytopenia after an upper respiratory tract infection, suggesting the diagnosis of primary immune thrombocytopenia, often occurring in pediatric patients. Due to the addition of symptoms suggesting a proliferative disease in this patient (pancytopenia, enlargement of lymph nodes, liver and spleen), a bone marrow biopsy was performed 11 months later, which did not confirm a hematopoietic tumor. Two years after the first symptoms appeared, the patient was referred for next-generation sequencing genetic testing, which confirmed the presence of a pathological CTLA-4 variant (c.356T>C). Due to the patient’s lack of response to the pharmacological treatment and the intensification of autoimmune symptoms that threatened the patient’s life, the patient underwent hematopoietic stem cell transplantation (HSCT) 34 months after the first occurrence of symptoms. After HSCT, the patient is alive and does not present any symptoms of autoimmunity.ConclusionsThe first symptoms of some diseases classified as inborn errors of immunity are non-specific and may delay the final diagnosis. Therefore, it seems extremely important that practicing pediatricians should take into account inborn errors of immunity in the differential diagnosis of autoimmune diseases.